Explaining the ranchers’ behavior of rangeland conservation in western Iran - Savari, Moslem (Frontiers in Psychology, 2023)
Rangeland are one of the most important natural habitats for the protection of living and non-living organisms. Degradation of rangeland is one of the biggest threats to biodiversity loss. Ranchers’, as the most important key stakeholders who have a direct relationship with rangelands, have put a lot of pressure on the rangeland sector in recent years, so that this natural habitat has been destroyed. Therefore, existing rangelands must be preserved to protect biodiversity. One of the most important strategies to protect rangeland is to change the behavior of ranchers to friendly and ecological behaviors in the environment. In this regard, this study was conducted with the general aim of explaining the ranchers’ behavior of rangeland conservation in western Iran. The main research tool was a questionnaire whose validity was confirmed by a panel of experts and its reliability was confirmed by Cronbach's alpha coefficient. In this study, value-belief-norm (VBN) was used to identify research variables. The results showed that ranchers have used different behaviors to protect rangelands and egoistic behaviors are the main cause of the destruction of this natural habitat. In addition, the results of this study showed that the framework used was an efficient theory because it explains 53.9% of rangeland conservation behavior. Finally, in this study, based on the research findings, applied policies for the protection of natural rangelands were presented so that in addition to rangeland conservation, biodiversity can also be preserved.